Inhibitory Deficits, Delay Aversion and Preschool AD/HD: Implications for the Dual Pathway Model. Issue 1 (2004) - Dalen, Lindy; Sonuga-Barke, Edmund J. S.; Hall, Martin; Remington, Bob
Abstract : The dual pathway model proposes the existence of separate and neurobiologically distinct cognitive (inhibitory and more general executive dysfunction) and motivational (delay aversion) developmental routes to AD/HD. The study reported in this paper explores the relation between inhibitory deficits and delay aversion and their association with AD/HD in a group of three-year-old children. Children identified as having a pre-school equivalent of AD/HD (N=19) and controls (N=19), matched for gender and IQ, completed a battery of inhibition and delay tasks. Correlational and factor analysis supported a dissociation between inhibitory deficits (go-no-go, set shifting) and delay aversion (choice delay) with delay of gratification cross-loading. Children with AD/HD displayed more inhibitory deficits and were more delay averse than controls. The data support the value of the distinction between motivational and cognitive pathways to AD/HD. Furthermore, the data suggest that such a distinction is apparent relatively early on during development.